WEB DASTURLASHNI O‘RGATUVCHI ZAMONAVIY VEB ILOVA ISHLASH CHIQISH TEXNOLOGIYASI - S.P. Kutliyev; I.J. Raximova; M.M. O‘ktamova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article helps students to understand the basic concepts of web programming in order to improve the quality of education. This involves guiding students through an interactive approach to understanding HTML, CSS, JavaScript, and other necessary tools.